2014
DOI: 10.1080/01443410.2014.895800
|View full text |Cite
|
Sign up to set email alerts
|

Testing two path models to explore relationships between students’ experiences of the teaching–learning environment, approaches to learning and academic achievement

Abstract: The study explores the relationships between students' experiences of the teaching-learning environment and their approaches to learning, and the effects of these variables on academic achievement. Two three-stage models were tested with structural equation modelling techniques. The Approaches and Study Skills Inventory for Students (ASSIST) and the Experiences of Teaching and Learning Questionnaire (ETLQ) were used to assess approaches to learning and student's experiences of the teaching-learning environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 71 publications
5
46
0
2
Order By: Relevance
“…In the Finnish data, six factors emerged from the 22 items measuring different aspects of quality teaching: (1) Teaching for understanding, (2) Alignment, (3) Staff enthusiasm and support, (4) Interest and relevance, (5) Constructive feedback, and (6) Support from other students (Parpala et al, 2013). This factor structure has also been identified among Greek students (Karagiannopoulou & Milienos, 2014). In line with previous research, Parpala et al (2013) found that the deep approach to learning scale was positively related to positive perceptions of the teaching-learning environment, whereas surface approach was negatively related to perception of the teaching-learning environment.…”
Section: Scales Measuring Teaching and Learning In The Surveymentioning
confidence: 64%
“…In the Finnish data, six factors emerged from the 22 items measuring different aspects of quality teaching: (1) Teaching for understanding, (2) Alignment, (3) Staff enthusiasm and support, (4) Interest and relevance, (5) Constructive feedback, and (6) Support from other students (Parpala et al, 2013). This factor structure has also been identified among Greek students (Karagiannopoulou & Milienos, 2014). In line with previous research, Parpala et al (2013) found that the deep approach to learning scale was positively related to positive perceptions of the teaching-learning environment, whereas surface approach was negatively related to perception of the teaching-learning environment.…”
Section: Scales Measuring Teaching and Learning In The Surveymentioning
confidence: 64%
“…The authors note that their findings differ from other studies using similar analytic approaches, which did find a positive relationship between a deep approach and achievement. Recent path analysis research by Karagiannopoulou and Milienos (2015), however, also failed to find a relationship between the deep approach and academic outcomes. Trigwell et al (2013) suggest the importance of using more sophisticated analytic approaches and more diverse variables when considering the relationships between approaches to learning and achievement.…”
Section: The Present Studymentioning
confidence: 99%
“…Este resultado se orienta en la misma dirección que otras investigaciones, la cuales concluyen que, o bien el modo en que los estudiantes se aproximan a las situaciones de aprendizaje no constituye un factor determinante del desempeño académi-co, o bien el tipo de acercamiento no tiene un efecto directo sobre el rendimiento, sino más bien indirecto (Al-Qahtani, 2015;Karagiannopoulou y Milienos, 2015). No obstante, dada la evidencia obtenida en este trabajo en las facultades de Ingeniería y Medicina, así como también la derivada de otros estudios que sí han hallado tal relación, resulta conveniente continuar indagando este punto en futuros desarrollos (Hasnor, Ahmad y Nordin, 2013;Salamonson et al, 2013;Svedin, Balter, Scheja y Pettersson, 2013).…”
Section: Discussionunclassified